2017
DOI: 10.1038/onc.2017.212
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Stearoyl-CoA-desaturase 1 regulates lung cancer stemness via stabilization and nuclear localization of YAP/TAZ

Abstract: Since the publication of the above article, the authors have noticed that the red line and the blue line were accidently inverted in the annotation inside Figure 6c. Red line should indicate β-cat_low/scd1_low, while blue line should indicate β-cat_high/scd1_high.The corrected Figure 6 is below.This correction has no effects on the results/conclusions of the paper.The authors would like to apologise to the readers for any inconvenience this may have caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Specifically, stearoyl coenzyme A desaturase 1 (SCD1), an enzyme involved in the conversion of saturated into unsaturated fatty acids, mediates the release of YAP/TAZ from the β-catenin destruction complex. The data from lung adenocarcinoma samples revealed that SCD1 co-expresses with nuclear YAP/TAZ suggesting a clear correlation between expression and activity of these genes, and thus with the desaturation index of the cell 85 87 . Although this link between YAP/TAZ-dependent unsaturation index of the cell and ferroptosis sensitivity has still not been investigated, studies showing that E-cadherin-dependent YAP/TAZ nuclear extrusion decreases the accumulation of lipid peroxides 69 71 , 73 suggest that this is something that deserves further and more in depth analysis.…”
Section: Cell-to-cell Contactmentioning
confidence: 99%
“…Specifically, stearoyl coenzyme A desaturase 1 (SCD1), an enzyme involved in the conversion of saturated into unsaturated fatty acids, mediates the release of YAP/TAZ from the β-catenin destruction complex. The data from lung adenocarcinoma samples revealed that SCD1 co-expresses with nuclear YAP/TAZ suggesting a clear correlation between expression and activity of these genes, and thus with the desaturation index of the cell 85 87 . Although this link between YAP/TAZ-dependent unsaturation index of the cell and ferroptosis sensitivity has still not been investigated, studies showing that E-cadherin-dependent YAP/TAZ nuclear extrusion decreases the accumulation of lipid peroxides 69 71 , 73 suggest that this is something that deserves further and more in depth analysis.…”
Section: Cell-to-cell Contactmentioning
confidence: 99%
“…This latter induces the activation of Wnt/ β -catenin signaling, and this axis, in turn, regulates the nuclear localization (activation) of YAP/TAZ, effectors involved in the Hippo pathway ( Figure 5 ). Such a correlation was also associated with poor prognosis in test samples of human lung adenocarcinoma [ 186 ]. Actually, YAP/TAZ are inducers of stem cell proliferation and survival and, in several cancers, their expression sustains tumor growth and invasion [ 187 , 188 ].…”
Section: Lipid Droplets In Cancer Stem Cellsmentioning
confidence: 99%
“…Next, in order to further confirm our observations, we evaluated the ability of VPA/SIM to affect YAP nuclear localization and activation, in 22Rv1 transiently transfected with either wild-type YAP (wt-YAP) or with the constitutively active mutated form YAP5SA [ 35 ] (Fig. 4 a).…”
Section: Resultsmentioning
confidence: 94%
“…Adherent 22Rv1 and 22Rv1 R_39 cells were transfected with YAP wild-type and YAP5SA plasmids as previously described by Noto A. et al [ 35 ] using Lipofectamine 2000 Reagents (Invitrogen, Carlsbad, CA, USA), according to the manufacturer’s recommendation. After 48 h from transfection, cells were collected and western blotting, real-time PCR and immunofluorescent experiments were performed as described before.…”
Section: Methodsmentioning
confidence: 99%